New Perspectives on International Functionalism
XIV, 181 p.
Keywords: This book reassesses international functionalism as an approach to global politics. Functionalism has been marginalized as simply a pre-scientific precursor to regional integration theory. In fact, functionalism provides a global view of states and international organizations working towards a peaceful and constructive world order through cooperative relationships across borders to satisfy human needs. Chapters examine the early development of functionalism and apply functionalist insights to issues, problems and conflicts in contemporary global governance.